Edukasi Mitigasi Bencana Banjir Di SMA 6 Gorontalo Utara Sebagai Upaya Peningkatan Kesiap Siagaan Bencana - Dewi Sartika Macmud; Fitryane Lihawa; Ramla Hartini Melo (Universitas Negeri Gorontalo, 2026)
Flooding is one of the most frequent hydrometeorological disasters in North Gorontalo Regency and may significantly disrupt safety and educational activities. SMA Negeri 6 Gorontalo Utara is located in a flood-prone area, making disaster mitigation education essential to improve students’ preparedness. This community service program aimed to enhance students’ knowledge and preparedness in dealing with flood disasters. The program was implemented through an initial field survey, educational counseling, and interactive discussions involving all students. The materials covered flood causes, flood impacts, and mitigation procedures before, during, and after flooding events. The results indicated an improvement in students’ understanding of flood mitigation, particularly in recognizing early warning signs, applying safety measures, and implementing preparedness actions within the school environment. This program contributed positively to strengthening disaster awareness culture at school and should be continued through evacuation drills and the establishment of a disaster-prepared school program.